2019
DOI: 10.1111/ejn.14601
|View full text |Cite
|
Sign up to set email alerts
|

Hand blink reflex in virtual reality: The role of vision and proprioception in modulating defensive responses

Abstract: Our research focused on the role of vision and proprioception in modulating a defensive reflex (hand blink reflex, HBR) whose magnitude is enhanced when the threatened hand is inside the peripersonal space of the face. We capitalized on virtual reality, which allows dissociating vision and proprioception by presenting a virtual limb in congruent/incongruent positions with respect to the participants' limb. In experiment 1, participants placed their own stimulated hand in far/near positions with respect to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This result is inconsistent with previous studies which showed that the sense of body-ownership increases more if human body-shaped avatar is presented compared to non-human body-shaped avatar 15 17 . It may be possible to embody one’s avatar even if the realism of the virtual body-representation is violated because simultaneous and congruent visuo-motor combination with the avatar strongly influences the embodiment 54 , 55 . In addition, there is another possibility that the discrepancies in body-ownership between the three groups that existed at the initial embodiment phase(i.e., 3-min break) may have disappeared after completing the task.…”
Section: Discussionmentioning
confidence: 99%
“…This result is inconsistent with previous studies which showed that the sense of body-ownership increases more if human body-shaped avatar is presented compared to non-human body-shaped avatar 15 17 . It may be possible to embody one’s avatar even if the realism of the virtual body-representation is violated because simultaneous and congruent visuo-motor combination with the avatar strongly influences the embodiment 54 , 55 . In addition, there is another possibility that the discrepancies in body-ownership between the three groups that existed at the initial embodiment phase(i.e., 3-min break) may have disappeared after completing the task.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality (VR) is a new technology that can give the illusion to be in another place, thanks to the so-called sense of presence (Sanchez-Vives and Slater, 2005), and to respond in a realistic way to virtual stimuli, including both physiological (Meehan et al, 2002;Tieri et al, 2015;Fossataro et al, 2020) and neural reactivity (Vecchiato et al, 2015a,b;Pavone et al, 2016), the so-called sense of agency, and even to do impossible or uncommon things, living unusual experiences, in a safe and controlled situation (Tieri et al, 2015), as often occurs in immersive videogames. Virtual reality has been suggested also as a useful tool in neurorehabilitation of patients because it may increase motivation and enjoy during therapy process (Cho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the illusory feeling of ownership and agency over the virtual body creates the necessary conditions to induce effects on the physiological (Martini et al, 2013;Kokkinara et al, 2016;Fossataro et al, 2020) or even components higher than the mere perceptual level, such as social (Peck et al, 2013;Banakou et al, 2018), neural (Seinfeld et al, 2021), or cognitive functions: concerning the latter, in our previous study, we demonstrated on young healthy participants acute improvement of cognitive (executive) functions after a high-intensity intermittent exercise performed exclusively by the considered-as-own virtual body (Burin et al, 2019c(Burin et al, , 2020. We argued that, despite the participants being completely still, the feeling of ownership and agency over the virtual body (only if displayed in a first-person perspective) (Kokkinara et al, 2016) induced a cascade of events (from the physiological activation of the heart rate to the increased neural activity over task-related areas), culminating in the improved cognitive performance immediately after the virtual exercise, comparable to what happens after a similar training performed by one's own physical body (Hyodo et al, 2016;Kujach et al, 2017).…”
Section: Introductionmentioning
confidence: 99%